Prediction bankruptcy models validation in Slovak business environment/Validacia predikcnych bankrotovych modelov v podmienkach SR - Delina, Radoslav; Packova, Miroslava (E+M ekonomie a management, 2013)
The prediction of bankruptcy has been the major subject of many studies since first study in this area, carried out by Fitz Patrick (1931). Many economists from all over the world have been trying to find company's bankruptcy forecasting model using different methods with the aim to achieve the best results. For this purpose discriminant analysis, probit and logit analysis have been usually used. As mentioned statistical methods needed to meet assumptions as linearity, normality and independence among predictor variables, new methods with nonlinear nonparametric properties such as neural networks have been developed and applied. Despite of many advantages of neural networks, still the above mentioned--classical statistical methods have been mostly used.